Scaling Milton Keynes power requirements for electrical transportation - Nieto-Martin, Jesus; Butans, Eugene; Correa-Castillo, Pablo; Fontaine, Jerome; Gonnelle, Alexis; Lahjibi, Mohamed; Vrancken, Carlos (Institute of Electrical and Electronics Engineers (IEEE), 2016)
Milton Keynes is home to the UK’s first installation of a wirelessly charged passenger bus route. This Inductive Power Transfer (IPT) system enables a fleet of 8 electric buses to service a demanding 15-mile urban route. Opportunistic wireless charging of the batteries during the layover time at the routes allows reducing the size of the batteries, consequently improving cost and performance characteristics of the bus. This paper aims to analyze the effects of electric buses on the electricity distribution grid. In particular, the paper analyses scalability of the IPT solution to all urban routes in Milton Keynes and compares peak power requirements generated at different points in the network with typical industrial and commercial (I&C) loads.
Keywords: Capacity Planning; Demand forecasting; Transportation; Technology planning